2003
DOI: 10.1159/000069894
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Intracerebral Hemorrhage in Northeast Malaysian Patients: A Four-Year Study

Abstract: The aim of this study was to compare nonsurgical versus stereotactic aspiration of intracerebral hematomas in relation to clinical aspects, computed tomographic imaging features of the brain, laboratory parameters and specific risk factors that may influence the outcome in southeast Asian Malay patients. Fifty-five of the patients with intracerebral hemorrhage (ICH) underwent stereotactic aspiration and 57 did not. Analysis was done on risk factors, locations and treatments of ICH, and the final outcomes measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 44 publications
1
3
1
Order By: Relevance
“…Although the data in this study showed non-statistical significance for mortality, the impact of disability-adjusted life years (DALY) is unarguable as the younger Malaysian population is developing ICH in Malaysia. Age was of no significance in predicting mortality ( P = 0.739) in this study, which was a similar finding from other studies ( 12 , 13 ).…”
Section: Discussionsupporting
confidence: 91%
“…Although the data in this study showed non-statistical significance for mortality, the impact of disability-adjusted life years (DALY) is unarguable as the younger Malaysian population is developing ICH in Malaysia. Age was of no significance in predicting mortality ( P = 0.739) in this study, which was a similar finding from other studies ( 12 , 13 ).…”
Section: Discussionsupporting
confidence: 91%
“…GOS and BI (the follow-up time was 122 weeks) was 4 and 90 respectively. ) were relatively larger than that of many other studies (8,14,23), the total rate of mortality was low (15.7%).…”
Section: Tang Zp Et Al: Modifying the Details Of Aspiration In Patiecontrasting
confidence: 57%
“…12 Alternative surgical procedures include craniotomy, endoscopic surgery and stereotactic aspiration, and various outcomes have been reported. 13,14 Minimally invasive techniques and early surgical intervention may be good options for patients with a significant volume of HPH. 4 The 3D reconstructed CT scan imaging technique could serve as a time-saving, simple, economic, and accurate method for targeting HPH, with no additional CT scanning needed thereafter for surgical planning.…”
Section: Resultsmentioning
confidence: 99%